2020
DOI: 10.1093/ijnp/pyaa002
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Ketamine Leads to Anxiety-Like Behaviors and Dysfunction in Bed Nucleus of Stria Terminalis

Abstract: Background Both the clinical and preclinical studies have suggested embryonic or infant exposure to ketamine, a general anesthetic, pose a great threat to the developing brain. However, it remains unclear how ketamine may contribute to the brain dysfunctions. Methods A mouse model of prenatal exposure to ketamine was generated by i.m. injection and continuous i.p. infusion of pregnant mice. Open field test and elevated plus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Expired CO2 concentration was increased in these exposed monkeys compared to control infants. Body temperature and blood glucose were not affected by the prenatal ketamine exposure (45).…”
Section: Physiologic Effects Of Ketamine Exposurementioning
confidence: 83%
See 2 more Smart Citations
“…Expired CO2 concentration was increased in these exposed monkeys compared to control infants. Body temperature and blood glucose were not affected by the prenatal ketamine exposure (45).…”
Section: Physiologic Effects Of Ketamine Exposurementioning
confidence: 83%
“…In humans, embryonic exposure to ketamine through pregnancy can create a great threat to brain development (45). Exposure to the neurotoxicity of ketamine has a greater effect on a developing brain than a mature adult brain (8,46,47).…”
Section: Neurobehavioral Effects Of Ketamine Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the anxiety effect might be mediated by various mode of actions of BuP. For example, narcotic activity is involved in parabens toxicity in invertebrates and fish (Dobbins et al, 2009) and prenatal exposure to narcotic substances causes anxiety (Sun et al, 2020). Narcosis is characterized by nonspecific disturbance of neuronal membranes integrity and functioning (Sandermann, 2008), which might persist also after the treatment ceased.…”
Section: Discussionmentioning
confidence: 99%
“…The authors interpret the OFT finding as an increase in risk-taking behavior and the EPM finding as an increase in anxiety. Sun et al38 examined the effects of early exposure to ketamine in mice and found avoidance in both the central zone of an OFT and in the open arms of an EPM with combined exposure to ketamine and dexmedetomidine and Turktan et al39 reported similar findings in mice with early exposure to dexmedetomidine. Two studies that examined EPM as part of a battery of behavioral tests reported te evidence of increased anxiety resulting from isoflurane and sevoflurane exposures 40,41.…”
Section: Update On Rodent Studies Of Anesthetic-induced Developmental...mentioning
confidence: 97%